Peran Industri Kerajinan Kain Perca dalam Meningkatkan Ekonomi Masyarakat - Linda Anita; Aliyudin Aliyudin; Ali Azis (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2020)
The purpose of this research is to find out the situation in the field related to the implementation, constraints and the results of empowerment of the patchwork handicraft industry in improving the economy of the community in Sukamulya Village. How is the implementation,constraints and empowerment of the patchwork industry in improving the community's economy. Th e method used in this study is a qualitative method by describing the situation in the field related to the implementation, constraints, and results of empowerment that have been made by the patchwork industry in improving the economy of the community. The results in this study are the implementation of the patchwork industry in improving the economy of the community carried out in the form of training programs. The obstacles faced by the patchwork industry in the empowerment process are internal and external factors. The results achieved in the empowerment of the patchwork handicraft industry are labor absorption, increased income, increased education, the community becomes more independent, and the economy of the Sukamulya Village community increases.